2023
DOI: 10.3390/coatings13071141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Bias Voltage on Microstructure and Mechanical Properties of Cr-Nb-Ti-Zr-N-O Ceramic Thin Films Produced by Reactive Sputtering

Abstract: Hard coatings are applied in various applications to protect substrates from wear and corrosion. In the present study, multi-element ceramic films are deposited by reactive sputtering. The level of substrate bias voltage (−50, −125 and −200 V) is changed to investigate the structural and mechanical properties of Cr-Nb-Ti-Zr-N thin films. Chemical analysis (using EDS, XRD and Raman spectroscopy) reveals that these thin films (with a high amount of oxygen) are composed of a nanocomposite phase structure (amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This method offers an excellent opportunity to produce homogeneous, smooth, and dense coatings with a rapid deposition rate, thereby increasing the coating-substrate adherence 59 , 60 . Additionally, multicomponent composite layers can be formed with precise control of the component concentrations by the magnetron co-sputtering 61 65 . For instance, previous research has demonstrated the successful use of TiN radio frequency sputtering in the coating of Ti-25Ta-xZr nanotube alloys for use in dental implants 66 .…”
Section: Introductionmentioning
confidence: 99%
“…This method offers an excellent opportunity to produce homogeneous, smooth, and dense coatings with a rapid deposition rate, thereby increasing the coating-substrate adherence 59 , 60 . Additionally, multicomponent composite layers can be formed with precise control of the component concentrations by the magnetron co-sputtering 61 65 . For instance, previous research has demonstrated the successful use of TiN radio frequency sputtering in the coating of Ti-25Ta-xZr nanotube alloys for use in dental implants 66 .…”
Section: Introductionmentioning
confidence: 99%